A Justification of Two-Dimensional Nonlinear Viscoelastic Shells Model - Fushan Li (Abstract and Applied Analysis)
By applying formal asymptotic analysis and Laplace transformation, we obtain two-dimensional nonlinear viscoelastic shells model satisfied by the leading term of asymptotic expansion of the solution to the three-dimensional equations.